Oral localized amyloidosis: a literary analisys and case report - Ferreira, Luciano Henrique; Campolina, Bruna Lavarini; Oliveira, Bruna Gomes dos Santos; Pedrosa, Bianca Aparecida Pacheco; Grandinetti, Helenice de Andrade Marigo; Capistrano, Hermínia Marques (Journal of Oral Diagnosis, 2022)
Introduction: Amyloidosis is a condition related to aggregates of proteins in several organs of the body and can be systemic or localized. Amyloidosis localized in the oral cavity is extremely rare, being the tongue the more prevalent region. Objective: The aim of this present study is to describe a case of localized amyloidosis on the tongue and surgically removed. Methods: Also, a review of English-language literature of oral loca-lized amyloidosis from 1946 to 2021 was performed. Results: A total of 52 cases of oral localized amyloidosis were found in the literature. The majority of the cases was observed in female patients (53,84%), with an average age of 55,4 years (range 9 to 90 years) and the tongue being the most common localization (49,12%). Conclusions: Amyloidosis is a rare condition with atypical sign and symptoms. The systemic involvement should be evaluated due to worse prognosis of this condition and the possibility of organs failures. There is no standard treatment for local amyloidosis, but surgical excision is indicated to reduce the functional prejudice and pain, in symptomatic cases.